Memórias de uma prática: experiência em oficina cognitiva para idosos - Sena, Teresa Christina da Cruz Bezerra de (2013)
This work aims to approximate between the fields of Social Gerontology, Cognition and Occupational Therapy, by proposing a cognitive intervention that considers the biography of subjects in an attempt to ownership of these elderly aging process. Supported in Freire's ideas about awareness and dialogue, we propose a reflection on the imposition of cognitive interventions for older people who disregard the knowledge and experiences gained from the systematization of a "Cognitive Workshop for Seniors" in a Living Center located on the premises a hospital in the city of Belém, State of Pará The workshop was developed in four modules, each with five meetings and two hours long, from March to September 2009, with a group of 33 healthy people with an average age of 71 4 years, ranging from 61 to 86 years, and 78.8% were female and 21.2% male. All subjects underwent a cognitive screening. Of the 33 participants, 48.5% were married, 42.4% widowed, 6.1% separated, and 3% were single, ie the majority, 51.5% had no marital bond; 75.8% had more than eight years of schooling. After the intervention, 45% continued to use much memory through reading (48%), games (27%), crafts (15%), daily exercises with use of writing and calculations (15%). The elderly have recognized that there are many techniques of remembrance or prevention of memory loss that retain the ability to handle your day-to-day. It was noted that the share memories provided a valuation of the elderly group, reflecting positively on cognition. We can point, among the findings of this research, the lack of attention as a possible cause of memory difficulties reported by seniors. Thus, cognitive interventions that consider the subject of the biography, the knowledge and experience accumulated throughout life, tend to have positive effects not only on cognition, but about self-esteem, enabling new forms of social integration of the elderly from the ownership of their aging process, extending actions and producing new ways of aging. The choice of the theme "Memories of a practice: experience in cognitive workshop for seniors" refers to all the paths followed since the first proposal organized by the researcher still lonely, until the final speech, a collective construction, which not only re-signified the life histories of these subjects but the "look" and the practice of professional